2022
DOI: 10.3390/app12083924
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless Amniotic Membrane Transplantation in Inflammatory Corneal Perforations

Abstract: Introduction: The aim of this study was to evaluate the efficacy of sutureless amniotic membrane transplantation (SAMT) in patients with corneal perforation secondary to ocular surface inflammatory diseases. Methods: Twelve eyes of eleven patients with corneal perforation associated with Sjögren’s syndrome and ocular cicatricial pemphigoid were included. Surgical procedure consisted in the application of two layers of amniotic membrane covering the corneal perforation and a therapeutic contact lens placed abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In a study in which the anterior chamber was lled with C3F gas in addition to hAM transplantation, the success rate was reported to be 100%. 7 Meduri et al 17 reported the e cacy of sutureless amniotic membrane transplantation in 12 eyes with in ammatory pathologies. They de ned the surgical procedure in their study as two layers of hAM and the application of a therapeutic contact lens on two layers, followed by striated seamless tarsorrhaphy, and reported resolution in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in which the anterior chamber was lled with C3F gas in addition to hAM transplantation, the success rate was reported to be 100%. 7 Meduri et al 17 reported the e cacy of sutureless amniotic membrane transplantation in 12 eyes with in ammatory pathologies. They de ned the surgical procedure in their study as two layers of hAM and the application of a therapeutic contact lens on two layers, followed by striated seamless tarsorrhaphy, and reported resolution in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients with severe corneal pathologies, such as chemical burns, autoimmune disease, Steven-Johnsons syndrome, and severe dry eye, amniotic membrane transplantation or corneal transplantation was mostly used in the past, but the curative effect was not ideal because of poor ocular surface conditions or inflammatory reactions caused by the sutures (1). Although it has been reported that the use of sutureless amniotic membrane transplantation improves the efficacy, large studies are still needed (2).…”
Section: Introductionmentioning
confidence: 99%